SEMIOTIC ANALYSIS ON NON-VERBAL LANGUAGE IN GADGET DIGITAL ADVERTISEMENT - Agustia, Km Tri Sutrisna; Kurniawan, Ida Bagus (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2022)
Objective. The purpose of non-verbal communication in a digital advertisement is to complete the informational delivery in the commercial itself. The utilization of certain circumstances in an advertisement cannot be isolated from the meaning of non-verbal language. With the help of semiotic analysis, this study seeks to explain the significance of non-verbal cues in two social media-sourced commercials for smartphones. Materials and Methods. This study's design employs a qualitative method for gathering data from research participants in the form of visual media from digital social media advertising for marketing tools. The study's objects are nonverbal behaviors like as facial expressions, gestures, body language, movement, touch, and look that can be seen in digital commercials. The purpose of non-verbal communication in a digital advertisement is to complete the informational delivery in the commercial itself. The utilization of certain circumstances in an advertisement cannot be isolated from the meaning of non-verbal language. With the help of semiotic analysis, this study seeks to explain the significance of non-verbal cues in two social media-sourced commercials for smartphones. Results. Semiotic rules can be used to interpret nonverbal language, but this interpretation needs to be backed by verbal language or other pertinent data. Conclusion. Semiotic meaning can be used to interpret how nonverbal communication is used in advertising. However, this needs to be backed up with more pertinent information and either spoken or visually explained in great detail.